EFEKTIVITAS PROGRAM KAMPUNG KELUARGA BERENCANA (KB) DAN DAMPAKNYA TERHADAP KESEJAHTERAAN KELUARGA MISKIN DI KOTA DENPASAR - Restiyani, Ni Luh Novi; Murjana Yasa, I Gusti Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.07.TAHUN 2019, 2019)
The purpose of this study was to determine and analyze the influence of wife education and the role of family planning officers on the effectiveness of the KB Village program and the welfare of poor families in Denpasar City. Sampling in this study was conducted accidentally sampling with a total sample of 81 poor families. Data was collected by observation and structured interviews which were then analyzed by path analysis techniques. The results of the study showed that the implementation of the KB Village program in Denpasar City was not yet effective. Wife education and the role of family planning officers have a positive and significant effect on the effectiveness of the KB Village program. This shows that the higher the wife's education and the more active the family planning officer, the more effective the KB Village program will be. Wife education has a positive and significant effect, while the role of family planning officers has a positive and not significant effect on the welfare of poor families. The effectiveness of the KB Village program has a positive and significant effect on the welfare of poor families in Denpasar City. The results also showed that wife education and the role of family planning officers indirectly affected the welfare of poor families in Denpasar City.